Gender-related persecution: an evaluation of the Asylum Adjudication process at the Department of Home Affairs in Cape Town - Rohde, Zoe (Centre for Law and Society, 2026)
Globally, women and girls represent approximately 50 per cent of the world's refugee population. They tend to be the most vulnerable group within this population and many face extreme hardship, including sexual violence, cruel and inhumane treatment, harassment and indifference not only in their countries of origin, but also during their journey and within the countries in which they seek protection. In general, in most societies women and girls tend to have less access than their male counterparts to fundamental rights, including access to shelter, food education and healthcare due to the unequal position that they occupy within these societies. During times of conflict and instability, discrimination and violence against women and girls tends to increase. The development of an international legal regime over the past 60 years has sought to ensure protection for those fleeing persecution, however, women and girls have been rendered largely invisible within it as well as within domestic status determination processes.